2008
DOI: 10.1093/pcp/pcn051
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Rab11a Characterization Evidenced a Difference Between SYP121-Dependent and SYP122-Dependent exocytosis

Abstract: The regulatory functions of Rab proteins in membrane trafficking lie in their ability to perform as molecular switches that oscillate between a GTP- and a GDP-bound conformation. The role of tomato LeRab11a in secretion was analyzed in tobacco protoplasts. Green fluorescent protein (GFP)/red fluorescent protein (RFP)-tagged LeRab11a was localized at the trans-Golgi network (TGN) in vivo. Two serines in the GTP-binding site of the protein were mutagenized, giving rise to the three mutants Rab11S22N, Rab11S27N a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 79 publications
(115 reference statements)
3
73
0
1
Order By: Relevance
“…Along with the Qa-SNARE SYP132, which is constitutively expressed and present at low levels (Enami et al, 2009), these proteins mediate secretory vesicle traffic, contributing to cellular homeostasis, expansion, and growth (Blatt, 2000;Shope et al, 2003;Campanoni and Blatt, 2007). Functional differences between SYP121 and SYP122 are known (Leyman et al, 1999;Zhang et al, 2007;Rehman et al, 2008;Honsbein et al, 2009Honsbein et al, , 2011Grefen et al, 2010a;Eisenach et al, 2012), but as these Qa-SNAREs share cognate partners Karnik et al, 2013b;Yun et al, 2013), studies to date have offered few clues to the mechanistic basis for the differences in their regulation and function. Among other factors, SM proteins are widely recognized to be key components that regulate SNARE-mediated vesicle traffic, both in stabilizing the cognate SNARE complex and in controlling the availability of several Qa-SNAREs for binding (Südhof and Rothman, 2009;Rizo and Südhof, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with the Qa-SNARE SYP132, which is constitutively expressed and present at low levels (Enami et al, 2009), these proteins mediate secretory vesicle traffic, contributing to cellular homeostasis, expansion, and growth (Blatt, 2000;Shope et al, 2003;Campanoni and Blatt, 2007). Functional differences between SYP121 and SYP122 are known (Leyman et al, 1999;Zhang et al, 2007;Rehman et al, 2008;Honsbein et al, 2009Honsbein et al, , 2011Grefen et al, 2010a;Eisenach et al, 2012), but as these Qa-SNAREs share cognate partners Karnik et al, 2013b;Yun et al, 2013), studies to date have offered few clues to the mechanistic basis for the differences in their regulation and function. Among other factors, SM proteins are widely recognized to be key components that regulate SNARE-mediated vesicle traffic, both in stabilizing the cognate SNARE complex and in controlling the availability of several Qa-SNAREs for binding (Südhof and Rothman, 2009;Rizo and Südhof, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The Qa-SNAREs of the plasma membrane are a case in point. In Arabidopsis thaliana, two of these SNAREs, SYP121 (=SYR1/PEN1) and SYP122, show a high degree of structural homology and overlap in function (Assaad et al, 2004;Tyrrell et al, 2007;Bassham and Blatt, 2008;Rehman et al, 2008). Single mutations of these Qa-SNAREs have little effect on plant growth under many conditions, and reduced growth is normally evident only in the syp121/syp122 double mutant (Assaad et al, 2004;Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Monitoring an exogenous reporter called secRGUS, it was possible to distinguish between SYP121 and SYP122 DN effects. The analysis of an exogenous marker, transiently expressed by the cells, certainly simplify the approach to this peculiar topic, where many genes appear to have functional redundancy just because a valid assay of their specificity is not available.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][10][11][12][13][14] For example, roles of small Rab-A GTPases, homologs of yeast Ypt31/32 and animal Rab11 in TGN trafficking to the cell plate in cytokinesis 10 and in polar secretion of cell wall components 6,7,13 have been demonstrated. Using a combined approach of genetic and in vivo imaging, we recently shown that Arabidopsis TRAPPII acts in intracellular trafficking in the TGN in root tip cells.…”
mentioning
confidence: 99%